1999
DOI: 10.1098/rspb.1999.0815
|View full text |Cite
|
Sign up to set email alerts
|

Genomic demography: a life-history analysis of transposable element evolution

Abstract: Retrotransposons are ubiquitous mobile genetic elements that have played a signi¢cant role in shaping eukaryotic genome evolution. The genome of the yeast Saccharomyces cerevisiae harbours ¢ve families of retrotransposons, Ty1^Ty5. With the publication of the S. cerevisiae genome sequence, for the ¢rst time a full genomic complement of retrotransposon sequences is available. Analysis of these sequences promises to yield insight into the nature of host^transposon coevolution. Evolutionary change in Ty elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 31 publications
2
33
1
Order By: Relevance
“…As shown in our results, the age of the full-length LTR retrotransposons in the D. melanogaster genome is substantially younger than the melanogaster species itself. Interestingly, the average ages of all fulllength LTR retrotransposons in yeast (<100,000 yr) (Promislow et al 1999) and nematode (<500,000 yr) (N. Bowen, unpubl. ) are also much younger than the age of the species in which they are contained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in our results, the age of the full-length LTR retrotransposons in the D. melanogaster genome is substantially younger than the melanogaster species itself. Interestingly, the average ages of all fulllength LTR retrotransposons in yeast (<100,000 yr) (Promislow et al 1999) and nematode (<500,000 yr) (N. Bowen, unpubl. ) are also much younger than the age of the species in which they are contained.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, LTR nucleotide identity has been used to estimate the time of insertion of LTR retrotransposons from S. cerevisiae, Zea mays, and humans. For example, the age of the Ty1 and Ty2 elements from S. cerevisiae has been estimated to be <100,000 years old (Jordan and McDonald 1999b;Promislow et al 1999). In contrast, it has been reported that the LTR retrotransposons within the ADH-region of the maize genome are much older, having transposed in the past 2 to 6 million years (SanMiguel et al 1998).…”
mentioning
confidence: 99%
“…LTR-LTR recombination has been measured for the Ty1-induced promoter mutation his4-912, and occurs at a rate of about 3 × 10 -6 per generation (Winston et al, 1984). Promislow et al (1999) have developed a novel "genomic demography" model to estimate long-term retrotransposition and LTR-LTR recombination rates for Ty1, Ty2, and Ty1/2 hybrid families and how long ago these elements entered the yeast genome. The computational approach resulted in similar Ty retrotransposition and loss rates of 8.67 × 10 -8 and 7.17 × 10 -8 per generation, respectively, which are much lower than those obtained experimentally.…”
Section: Ty Copy Numbermentioning
confidence: 99%
“…The levels of Ty1AS RNA and mRNA varied between the repopulated S. paradoxus strain and S. cerevisiae, suggesting that expression levels may be species or element-specific. Our results show that genomic Ty1AS RNAs are produced in a copy-dependent manner in two different genomic environments; a repopulated genome containing essentially identical copies of recent Ty1-H3 transposition events (15), and a S. cerevisiae strain whose natural history with respect to Ty1 is more complex (22)(23)(24).Ty1 transposition at preferred integration targets was determined using a qualitative PCR-based assay in strains with different Ty1 copy numbers (Fig. S1B).…”
mentioning
confidence: 99%